Remarks by Sean D. Murphy. (2020) - Murphy, Sean D.
Abstract : Our conversation might begin by looking backward a bit. The human rights movement from 1945 onward has been one of the signature accomplishments of the field of international law, one that refocused our attention from a largely interstate system to a system where the individual moved in from the periphery to the center. Human rights champions point to numerous landmark treaties, numerous institutions, and the rise of NGOs as a critical vehicle for developing and monitoring human rights rules. Yet others look at the international human right system and still see the state as overly central, tolerating and paying lip service to human rights, but too easily discarding them when they prove to be inconvenient. The persistence of racism comes to mind. As a general matter, how would you assess the strengths and weaknesses of the system that was built essentially during your lifetime?